BASIC TENDENCIES AND PROBLEMS IN DEMOGRAPHIC DEVELOPMENT OF AGRICULTURAL POPULATION OF SERBIA - Raduški, Nada (Economics of Agriculture, 2008)
The end-result of the complex and contradictory processes taking place in the agriculture throughout the period since the Second World War is depopulation and persistent crisis in agriculture. Mass transfer of rural population to cities and transition from agricultural to non-agricultural activities has had a series of negative demographic, economic, sociological, cultural and others consequences. The decline in agricultural population (from 66.0% in 1953. to 10.9% in 2002.) is one of the most significant change in the social and economic structure of population in Serbia. Due to the characteristic migration patterns by age and sex, they have had a substantial impact on the change in age-sex structure of agricultural population (increasing share of women and old generations). Feminization and senilization of village practically left them without labor force, while agricultural became a neglected activity.